2008
DOI: 10.1063/1.2939434
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic modification of infrared response in gated structures based on VO2

Abstract: Abstract:We investigate the changes in the infrared response due to charge carriers introduced by electrostatic doping of the correlated insulator vanadium dioxide (VO 2 ) integrated in the architecture of the field effect transistor. Accumulation of holes at the VO 2 interface with the gate dielectric leads to an increase in infrared absorption. This phenomenon is observed only in the insulator-to-metal transition regime of VO 2 with coexisting metallic and insulating regions.We postulate that doped holes lea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 26 publications
1
47
0
Order By: Relevance
“…Although previous researchers have suggested that field or carrier injection alone may be sufficient to induce the transition 21,22 , evidence suggests that in our experimental geometry the transition results most directly from Joule heating. At room temperature, the local power injection immediately prior to the insulatorto-metal transition shown in Fig.…”
mentioning
confidence: 67%
“…Although previous researchers have suggested that field or carrier injection alone may be sufficient to induce the transition 21,22 , evidence suggests that in our experimental geometry the transition results most directly from Joule heating. At room temperature, the local power injection immediately prior to the insulatorto-metal transition shown in Fig.…”
mentioning
confidence: 67%
“…The nature of the electronic and structural phase transition has been a matter of research and debate for over three decades, with many recent experiments shedding additional light on the issue 6,7,8,9,10,11,12,13,14,15 . But during this period the hysteretic nature of VO 2 has received much less attention.…”
Section: Introductionmentioning
confidence: 99%
“…The hybrid-metamaterial approach (5,6), wherein natural materials are integrated into the metamaterial composite, has been particularly successful in enabling frequency-agile metamaterials which respond to application of voltage (7,8), external electric field (9), light (10,11), and heat (12). This tuning ability helps make metamaterial devices more versatile, adapting to shifting input or changing target parameters.…”
mentioning
confidence: 99%